2017
DOI: 10.3748/wjg.v23.i29.5333
|View full text |Cite
|
Sign up to set email alerts
|

Salvianolic acid B protects hepatocytes from H2O2injury by stabilizing the lysosomal membrane

Abstract: AIMTo investigate the capability of salvianolic acid B (Sal B) to protect hepatocytes from hydrogen peroxide (H2O2)/carbon tetrachloride (CCl4)-induced lysosomal membrane permeabilization.METHODSCell Counting Kit-8 assay was used to measure cell viability. Apoptosis and death were assayed through flow cytometry. BrdU incorporation was used to detect cell proliferation. Serum alanine aminotransferase activity and liver malondialdehyde (MDA) content were measured. Liver histopathological changes were evaluated u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(24 citation statements)
references
References 47 publications
1
23
0
Order By: Relevance
“…ROS can also damage mitochondria and induce apoptosis by affecting lysosomal membrane permeability to release of hydrolase (Gao C. et al, 2014). In the H 2 O 2 -induced apoptosis of BNL CL.2, a mouse liver cell line, Sal B can stabilize lysosomal membranes by increasing the expression of lysosomal-associated membrane protein 1 and antagonizing cathepsin B/D leakage into the cytoplasm (Yan et al, 2017). These results indicate that both the death receptor pathway and the mitochondrial pathway are related to excess ROS overdose, and the inhibitory effect of Sal B on these two classical apoptotic pathways may be a continuation of its antioxidant effect.…”
Section: Classical Apoptotic Pathwaymentioning
confidence: 99%
“…ROS can also damage mitochondria and induce apoptosis by affecting lysosomal membrane permeability to release of hydrolase (Gao C. et al, 2014). In the H 2 O 2 -induced apoptosis of BNL CL.2, a mouse liver cell line, Sal B can stabilize lysosomal membranes by increasing the expression of lysosomal-associated membrane protein 1 and antagonizing cathepsin B/D leakage into the cytoplasm (Yan et al, 2017). These results indicate that both the death receptor pathway and the mitochondrial pathway are related to excess ROS overdose, and the inhibitory effect of Sal B on these two classical apoptotic pathways may be a continuation of its antioxidant effect.…”
Section: Classical Apoptotic Pathwaymentioning
confidence: 99%
“…As previously reported, H 2 O 2 treatment induced lysosome destabilization. 34 We next investigated the effects of PTL on the lysosomes damage. It is known that lysosomotropic reagent LLME induces lysosomal membrane permeabilization, 35 but the PTL actions in LLMEinduced lysosomes damage has not been investigated.…”
Section: Ptl Prevents H 2 O 2 -Induced Lysosomes Damage In C2c12 Cellsmentioning
confidence: 99%
“…Although Sal B has been reported a variety of bene cial metabolic effects including ameliorated the histopathological alterations of pancreas, increased muscle glycogen content, increased p-AMPK protein expression in skeletal muscle and liver; increased protein expressions of PPARαand p-ACC in liver. [17,18] Our study showed that Sal B reduced intracellular accumulation of LDs and TG level whereas stimulated autophagosome formation by increasing expression of autophagosome formation marker LC3 II and decreasing autophagy substrates marker p62 expression in hepatocytes. Meanwhile, Beclin-1, another aytophagy biomarker which mainly activated autophagy by formation of class III PI3-kinase complex to stimulate ATG proteins, was found signi cantly higher expression in Sal B treated hepatocytes.…”
Section: Discussionmentioning
confidence: 63%
“…[13][14][15][16] In hepatocytes, Sal B has been reported a strong ability to protect cells from injury induced by oxidative stress, in ammation and enhance hepatic differentiation. [17][18][19] However, the effect of Sal B on improving hepatic lipid disorder is rarely reported. In this study, we interestingly found that Sal B could stimulated hepatic autophagy while reduced lipid accumulation in hepatocyte, which indicated a possible mechanism for Sal B improved lipid disorder and contributed to metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%